PERAN DINAS KOMUNIKASI DAN INFORMATIKA KOTA SERANG DALAM PENYEBARLUASAN INFORMASI DAN TATA KELOLA PEMERINTAH DAERAH - Dewi, Lia Riesta; Furqon, Eki (Department of Constitutional and Administrative Law, Faculty of Law Universitas Negeri Semarang (UNNES)., 2020)
This article aims to analyze the objective condition for disseminating information on development performance and governance in the Serang City Government? What are the obstacles and obstacles for the City of Serang Communication and Information Technology in disseminating information on the development performance and governance of the Serang City Government? Where the current millennial era certainly requires information technology support, for example, by using the internet as an instrument for disseminating information by using online or online-based support. This study uses a qualitative research method with a normative juridical and empirical juridical approach. The information dissemination system needs a sustainable effort in structuring instrument by implementing the use of information technology as an intermediary and a more coordinated and consolidated chain of information dissemination, as well as stimulating the acceleration of the presence of smart government as a support for the realization of an informative society in Serang City. Of legal protection that is just, harmonious, and under the State Administrative Court Law and the 1945 Constitution of the Republic of Indonesia as the basis of the Indonesian state.